Organization of Individual Work of Students – Future Bachelors of Nursing Based on Using the Information and Communication Technologies - Demianchuk, Mykhailo; Oliinyk, Nadiia (Pedagogical Discourse, 2021)
The importance of organization of individual work of students – future bachelors of nursing based on using information and communication technologies has been analysed. Studies in the field of using the information and communication technologies in the vocational education have more than 30 years of history. During this time, many attempts have been made to introduce a variety of information products in the educational process, including the training of future bachelors of nursing. Due to the rapid progress of information technologies the process of informatization of education and health care optimizes the extensive infrastructure of electronic information resources, which are actively used in the activities of medical institutions. The expediency of organization of individual work of future bachelors of nursing by means of the ICT is confirmed by the modernization of digital processes taking place in the institutions of higher medical education. Among the important tasks of digitalization of Ukrainian health care should be noted the creation of innovative services and platforms, including diagnostic, which provide remote interpretation and evaluation of the quality of medical research results, ensuring the transition to personalized medicine. It has been established that in the conditions of informatization of medical education and implementation of competence approach in higher education to increase the effectiveness of individual work of students directed to the formation of readiness of future bachelors of nursing to use the ICT in professional activities, may be possible on the basis of systematically using the ICT and developing the complex of interdisciplinary electronic projects. The logic of implementation of interdisciplinary electronic projects into educational process of medical academy for organization and effective management of individual work of students, is reflected in four interrelated stages, that are: organizational and preparatory, the main task of which was the organization of procedures for pedagogical examination of the goals, essence and criteria for evaluating the individual work of future bachelors of nursing in the implementation of interdisciplinary electronic projects; technological, which involved the development of a system of projects and e-courses; creation of diagnostic materials (questionnaires and tests) for evaluating the effectiveness of research work; experimental, which included entrance testing and counseling of students, organized seminars, tested the author’s interdisciplinary e-projects in e-courses through the purposeful use of the ICT; final, which involved analysis and correction of the obtained results.